7(x+3)-(4x-9)=8

Simple and best practice solution for 7(x+3)-(4x-9)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+3)-(4x-9)=8 equation:


Simplifying
7(x + 3) + -1(4x + -9) = 8

Reorder the terms:
7(3 + x) + -1(4x + -9) = 8
(3 * 7 + x * 7) + -1(4x + -9) = 8
(21 + 7x) + -1(4x + -9) = 8

Reorder the terms:
21 + 7x + -1(-9 + 4x) = 8
21 + 7x + (-9 * -1 + 4x * -1) = 8
21 + 7x + (9 + -4x) = 8

Reorder the terms:
21 + 9 + 7x + -4x = 8

Combine like terms: 21 + 9 = 30
30 + 7x + -4x = 8

Combine like terms: 7x + -4x = 3x
30 + 3x = 8

Solving
30 + 3x = 8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + 3x = 8 + -30

Combine like terms: 30 + -30 = 0
0 + 3x = 8 + -30
3x = 8 + -30

Combine like terms: 8 + -30 = -22
3x = -22

Divide each side by '3'.
x = -7.333333333

Simplifying
x = -7.333333333

See similar equations:

| 4(5+2q)=-4+5q | | -6(-1x+8)=18 | | x^2-50=-1 | | 65-34.3=x | | x-9=3x-11 | | -56=7+7x | | 9-3x=7x+19 | | 8(x+7)-(5x-9)=1 | | .37+1.1m=2.65m-1.18 | | 4x+18=34 | | 11x+5x-1=32 | | -5x-7=41-x | | 2.4=16x | | 12(1.15)= | | y*6=3.3 | | 4x^2+20x+12=x+20 | | x+6=-7x+86 | | 1/2(x+4)=1/3(3x-6) | | -3(-2x+7)=-81 | | x+31=78 | | 3-3.7(8-x)=16.5 | | 19=2a-(a+1) | | 7x-56=9-3x+5-4x | | n-40=47 | | 4y=28 | | -11-5=(5x+4) | | z-9=4 | | x^4+2x^3+1=0 | | 23=m+36 | | 8y+5=7y-5 | | .25d= | | 5(3x+9)=37 |

Equations solver categories